2022
DOI: 10.1186/s41155-022-00222-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the FACES IV package for Spanish adolescents

Abstract: The family plays an essential role in the life of an adolescent. Hence, an acceptable understanding and an evaluation of family functioning is fundamental for effective interventions with adolescents in the psychological, social, and educational fields. The main purpose of this study is to examine the psychometric properties of the Family Adaptability and Cohesion Evaluation Scale (FACES IV), the Family Communication Scale (FCS), and the Family Satisfaction Scale (FSS), for assessing the family functioning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The four unbalanced scales comprise two for cohesion (disengaged and enmeshed) and two for flexibility (rigid and chaotic). It may be noted that there is a significant body of research devoted to adapting FACES IV in various contexts and assessing their psychometric properties (Martínez-Pampliega et al, 2017; Olson, 2011; Priest et al, 2020; Rivero et al, 2010; Sarour & El Keshky, 2022; Türkdoğan et al, 2018; Vegas et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The four unbalanced scales comprise two for cohesion (disengaged and enmeshed) and two for flexibility (rigid and chaotic). It may be noted that there is a significant body of research devoted to adapting FACES IV in various contexts and assessing their psychometric properties (Martínez-Pampliega et al, 2017; Olson, 2011; Priest et al, 2020; Rivero et al, 2010; Sarour & El Keshky, 2022; Türkdoğan et al, 2018; Vegas et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Positive communication not only stabilizes family structures and improves family relationships, but also fosters healthy family behaviors, which are a key measure for effectively preventing mental health problems in adolescents. A cross-sectional survey of Spanish adolescents found that mastery of communication skills and open communication can improve family relationships by increasing cohesion and exibility within the family structure [14]. Furthermore, family communication can also reduce domestic violence and internet addiction, thus effectively preventing mental health problems such as autism and personality disorders in young people [15][16].…”
Section: Introductionmentioning
confidence: 99%